2023
DOI: 10.20525/ijrbs.v12i2.2354
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of ESG issues on investment decision through corporate reputation: Individual investors’ perspective

Abstract: Whether investors take into account a company's environmental, social, and governance (ESG) issues when making investment decisions (ID), how they interpret corporate reputation (CR) as a result of ESG issues, and whether CR mediates the relationship between ESG issues and ID are the goals of this study. The theory of planned behavior (TPB) and the signaling theory are the bases of the framework. The study was based on a questionnaire survey that received 599 responses from active retail investors in two Bangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Moreover, while the academic community has not directly discussed the connection between ESG and reputation, studies have already demonstrated that a company's reputation plays a mediating role in the relationship between ESG performance and debt costs [ 28 ]. Additionally, corporate reputation has been shown to mediate the significant positive impact of ESG on investment decisions [ 29 ]. These findings provide evidence for the significant relationship between ESG performance and company reputation that this article urgently seeks to explore.…”
Section: Literature Review and Theoretical Analysismentioning
confidence: 99%
“…Moreover, while the academic community has not directly discussed the connection between ESG and reputation, studies have already demonstrated that a company's reputation plays a mediating role in the relationship between ESG performance and debt costs [ 28 ]. Additionally, corporate reputation has been shown to mediate the significant positive impact of ESG on investment decisions [ 29 ]. These findings provide evidence for the significant relationship between ESG performance and company reputation that this article urgently seeks to explore.…”
Section: Literature Review and Theoretical Analysismentioning
confidence: 99%